Colleters in rubiaceae from forest and savanna: The link between secretion and environment - Tresmondi, Fernanda [UNESP]; Canaveze, Yve [UNESP]; Guimarães, Elza [UNESP]; Machado, Silvia Rodrigues [UNESP] (Springer Nature, 2017)
This study aims to investigate colleters’ secretory function, on cellular level, in Rubiaceae species from contrasting environments looking to explore the association between secretion and environment. We collected samples from eight species of Rubiaceae growing in forest and savanna having standard-type colleters with diverse histochemistry (hydrophilic, lipophilic and mixed secretions) and processed for both conventional and cytochemical study under transmission electron microscopy (TEM). The standard colleters, although similar in morphology and anatomy, exhibited marked differences on cellular level, especially in the abundance and topology of Golgi bodies, endoplasmic reticulum and plastids when comparing forest and savanna species. These differences were clearly aligned with the chemical nature of the secretions they produce, with predominance of hydrophilic secretions in forest species and lipophilic or mixed secretions in savanna species. The combination of methods in electron microscopy revealed the sites of synthesis and intracellular compartmentation of substances, the mechanisms of their secretion from the protoplast and confirmed the involvement of the outer walls of the epithelial cells in the elimination of exudates to the gland surface. Our study suggests a potential environment-associated plasticity of the secretory cells of standard-type colleters in modulating their secretory function performance.
Keywords: Colleters; Cytochemistry; Functional plasticity; Rubiaceae; Secretion; Ultrastructure